1998
DOI: 10.1175/1520-0469(1998)055<1909:solhff>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Latent Heat Flux from PILPS Land-Surface Schemes to Perturbations of Surface Air Temperature

Abstract: In the PILPS Phase 2a experiment, 23 land-surface schemes were compared in an off-line control experiment using observed meteorological data from Cabauw, the Netherlands. Two simple sensitivity experiments were also undertaken in which the observed surface air temperature was artificially increased or decreased by 2 K while all other factors remained as observed. On the annual timescale, all schemes show similar responses to these perturbations in latent, sensible heat flux, and other key variables. For the 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Important is that changes of HRLDAS latent heat and sensible heat flux are not linear with respect to the change of air temperature, consistent with the work of Qu et al (1998). For instance, decreasing air temperature in HRLDAS resulted in greater differences in surface fluxes and soil moisture than increasing air temperature, and similar results apply to other forcing variables.…”
Section: Hrldas Response To Atmospheric Forcing Conditionsmentioning
confidence: 54%
See 1 more Smart Citation
“…Important is that changes of HRLDAS latent heat and sensible heat flux are not linear with respect to the change of air temperature, consistent with the work of Qu et al (1998). For instance, decreasing air temperature in HRLDAS resulted in greater differences in surface fluxes and soil moisture than increasing air temperature, and similar results apply to other forcing variables.…”
Section: Hrldas Response To Atmospheric Forcing Conditionsmentioning
confidence: 54%
“…Qu et al (1998) studied the sensitivity of latent heat flux to variations of surface air temperature, and Luo et al (2003) used two sets of forcing conditions (NCEP EDAS and station observations) in NLDAS experiments to investigate differences in NLDAS output caused by differences in these two sets of forcing conditions. Nevertheless, the LSM response of surface heat fluxes, soil moisture, and soil temperature to each of the forcing variables has not been systematically explored in the past.…”
Section: Hrldas Response To Atmospheric Forcing Conditionsmentioning
confidence: 99%
“…Phase 2(a) focused on the partitioning between sensible and latent heat fluxes for a grassland site at Cabauw, Netherlands (Chen et al 1997), and the response of simulated heat fluxes to changes in air temperature (Qu et al 1998). The analysis revealed that, for the Cabauw site, consideration of the stomatal control and soil-moisture stress formulations among the LSSs was crucial to the interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the API method, much tuning of the weighting parameter is usually needed for each location, while the lack of direct observations may prevent effective tuning at most locations. For the LDAS approach that involves extended model runs, the final analyses depend on the skill/quality of the land model [8,9] and also on model forcing errors.…”
Section: Introductionmentioning
confidence: 99%